From the European Medicines Agency to Project Orbis: new activities and challenges to facilitate UK oncology drug approval following Brexit. Issue 4 (April 2023) - Lythgoe, Mark P; Krell, Jonathan; Bower, Mark; Murphy, Ravindhi; Marriott, John; Blagden, Sarah P; Aggarwal, Ajay; Sullivan, Richard
Summary: The departure of the UK from the European Union (EU) and affiliated European regulatory bodies, including the European Medicines Agency, on Dec 31, 2020, has resulted in the Medicines and Healthcare products Regulatory Agency becoming an independent national regulator. This change has required a fundamental transformation of the UK drug regulatory landscape, creating both opportunities and challenges for future development of oncology drugs. New UK pharmaceutical policies have sought to make the UK an attractive market for drug development and regulatory review, by offering expedited review pathways coupled to strong collaborative relations with other leading international medicines regulators, outside of Europe. Oncology is a key global therapy area for both drug development and regulatory approval, and the UK Government has been keen to show regulatory innovation and international collaboration through approval of new cancer medicines. In this Policy Review, we examine the new UK regulatory frameworks, policies, and global collaborations affecting new oncology drug approvals after departure from the EU. We explore some of the challenges that might lie ahead as the UK creates new and independent regulatory review and approval processes for the next generation of cancer medicines.